An algorithm for probabilistic solution of parabolic PDEs. Issue 4 (2nd October 2021) - Haneche, M.; Djaballah, K.; Khaldi, K.
Abstract: The aim of this work is to approximate the trajectory solution of parabolic partial differential equations (PDEs) by the probabilistic method. This method is based on the representation of Feynman-Kac and Monte Carlo methods. As an alternative to classical Monte Carlo, here we employ quasi–Monte Carlo methods and propose some solutions to the problem of using this alternative through a more efficient algorithm than the classics.